Music Therapy for Delinquency Involved Juveniles Through Tripartite Collaboration: A Mixed Method Study - Chong, Hyun Ju; Yun, Juri (Frontiers in Psychology, 2020)
This study introduces a music therapy project for young offenders through community collaboration and its efficacy through a mixed method. The project called Young & Great Music is carried out via collaboration among three parties, which are the educational institution, the district prosecutor’s office, and corporate sponsor, forming a tripartite networking system. In this paper, we present an efficacy evaluation of the project’s implementation with 178 adolescents involved with the juvenile justice system: 115 youth was on suspension of indictment and 63 youth was under supervised probation. Quantitative and qualitative measures were collected and analyzed to examine the efficacy of the project. The music therapy program was developed for 15 sessions based on the use of music to prompt positive resources through music making and song writing. The efficacy was examined using three scales; self-concept, resilience, and stress coping skills. The paired t-test showed that there were significant improvement in all three scales respectively (p< .000). In order to examine the group difference between suspended indictment and supervised probation groups, Welch-Aspin t test was conducted due to unequal variance of the group. Results showed there was a significant group difference in self-concept (p= .006) and resilience (p= .022). The study further examined participant's experience of music and perceived benefits. Twenty participants had in-depth interviews about their music therapy experience which were recorded, transcribed and analyzed. Of the 109 statements derived from a qualitative content analysis of the interview transcripts, music making and song writing was repeatedly reported as helpful in gaining “new perspectives,” “courage to challenge and pursuit,” “perseverance,” and “self-acknowledgement.” The positive result of the study showed that the collaborative networking of regional and social resource to support for adolescents at-risk was successful. The results of this project are promising and suggest that other arts-based rehabilitation services and programs should be developed and implemented in juvenile justice system. For this, strategies for program sustainability for long-term facilitation are needed.